Методи оцінки якості синхронізації аудіо та відео на основі нейронних мереж - Мирошник, Ю. Ю.; Рябова, Н. В. (ХНУРЕ, 2025)
This thesis analyses the impact of audiovisual synchronisation on the realism of digital avatars used in film dubbing, video conferencing and digital assistants. Accurate lip-audio alignment is highlighted as a key factor in achieving natural, Comparative attention is given to specialised lip-sync models (e.g. SyncNet) and advanced multimodal approaches (e.g. AV-HuBERT). The results show that stable synchronisation significantly improves audience engagement and reduces visual inconsistencies. Practical applications in multilingual face-dubbing illustrate the potential and limitations of current methods.
Keywords: синхронізація аудіо та відео; оцінка якості синхронізації